Kinetics and Mechanism of Decomposition of Hydrogen Peroxide Catalyzed by fat Co3+and [Co(NH3)4]3+ Adsorbed on Alumina - MISHRA, PARASHURAM (Asian Journal of Chemistry, 2010)
The decomposition of H2O2 at 30° catalyzed by Co3+ ions, adsorbed on alumina, exhibits first order kinetics with respect to [H2O2]. As the amount of surface adsorbed ions increases, the value of first order rate constant initially increases linearly, reaches a maximum and decreases thereafter. It is found that pH greatly influences the decomposition of H2O2 consistent with the kinetic data.